Interpersonal coordination analysis of tennis players from different levels during official matches - Costa Pereira, T. J.; van Emmerik, R. E. A.; Shoiti Misuta, M.; Barros, R. M. L.; Arruda Moura, F. (Journal of Biomechanics, 2018)
The purpose of this study was to assess the interpersonal coordination during official male tennis matches in players of different skill levels. Players` trajectories of three levels (Juvenile, ATP-Future, ATP-250) were obtained using video-based tracking system. A vector coding technique was applied to obtain players` interpersonal coordination in four coordination patterns: "anti-phase", "in-phase", "serving player phase" and "returning player phase". These patterns allowed identification of the nature of the coupling and lead/lag relations between players. In all categories, players presented higher degree of "anti-phase" and "serving player phase" (when only the serving player is moving on the court or his opponent is moving with a time lag) coordination. Young players spent more time in "serving player phase" during lateral displacements than professional players. On the other hand, professional players spent more time in "returning player phase" (when only the returning player is moving on the court or his opponent is moving with a time lag) during antero posterior displacements, than young players. Interpersonal coordination did not change from the first to the second set of the match, showing that tennis players maintain their displacement characteristics and strategy, independently of proficiency level. The vector coding technique allowed to identify new coordination patterns in tennis, providing additional information about tennis dynamics and how players from different categories and proficiency levels behave during the matches.